The Influence of Online Attendance System and Work Discipline on The Performance of Educational Staff in Universitas Negeri Semarang - Endang Retno Pujirahayu; Sutikno Sutikno; Nur Hidayat (Universitas Negeri Semarang, 2023)
This research is aimed at understanding the influence of the online attendance system and work discipline on the performance of educational staff at Universitas Negeri Semarang (UNNES). The sampling technique employed in this research is random sampling, where the researcher randomly took samples without considering the variety of the population’s background. There were 140 (20%) Educational Staff in UNNES taken as the samples of this research. This research features a quantitative approach where the primary data were obtained from surveys through questionnaires distributed to the respondents. The data analysis and processing utilised the regression equation in the SPSS, a statistics software. The problems underlying this research are formulated as follows: Do the online attendance system and work discipline significantly influence the performance of educational staff in Universitas Negeri Semarang? The result shows that the main factor influencing employees' work performance in UNNES is work discipline. The implementation of an online attendance system has minimum influence on employees’ performance. Online attendance systems, followed by work discipline, directly had a more significant impact than merely the online attendance systems.